GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DISIPLIN KERJA SEBAGAI VARIABEL MEDIASI - RECKY, RECKY; WIDYAWATI, WIDYAWATI; NAZARUDDIN, NAZARUDDIN (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
This study aims to analyze the effect of leadership style on employee performance, analyze the influence of leadership style on work discipline, analyze the influence of work discipline on performance, analyze whether work discipline is a mediating variable between leadership style on performance at PT. Bandar Victory Shipyard. The population of this study were all employees of the product department, totaling 83 people. The data collection method used was a questionnaire. Data analysis technique using PLS-SEM. Based on the research results, it can be concluded that there is a significant influence of leadership style on employee performance. There is a significant influence of leadership style on work discipline. There is a significant influence of work discipline variables on employee performance. There is an influence of leadership style on performance with work discipline as a mediating variable.